Operational Regimes of Input Filters - Rodionova, I.; Raņķis, I. (Elektronika ir Elektrotechnika, 2005)
In this paper an investigation of the L,C filter at output of the single-phase uncontrolled rectifier is done. Equations describing processes in such a filter and are providing possibility to calculate parameters of elements are obtained. Computer simulation realized for filter accepts a results of mathematical investigation. Calculated parameters of the equipment – the mass of reactor for different operational regimes and current of load are estimated. Is evaluated also an impact of the filter on harmonic distortion of the networks current. Is shown that THD indicator is very close to the figure 0.4 and in very small extent depends on level of reactor’s current pulsation. Ill. 7, bibl. 4 (in English; summaries in Lithuanian, English, Russian).